KAJIAN HUKUM PELAKSANAAN PROGRAM PEMBAHARUAN AGRARIA NASIONAL DI KABUPATEN SERDANG BEDAGAI - PUTRI AYU REZKI UTAMI (PREMISE LAW JURNAL, 2014)
ABSTRACT Today, our country is facing structural problems, such as high unemployment, high ranking in poverty, high concentration on agrarian assets in the minority of the people, the problems of dispute and conflict throughout Indonesia, the susceptibility of food security, the decrease in the quality of environment, and the poor condition of families’ economy. In order to cope with these problems, the government, through BPN (the National Land Agency) has formulated 11 (eleven) prioritized agendas which are framed in an Agrarian Reformation which is called National Agrarian Reform Program (PPAN). The Land Office of Serdang Bedagai District has implemented PPAN since 2008 and has issued 24,000 certificates through this PPAN. Therefore, the problems of the research were as follows: how about the legal policy of PPAN in the post-reformation era, how about the implementation of PPAN in Serdang Bedagai District, and what factors which became the obstacles and how about the solution of the problems in the implementation of PPAN in Serdang Bedagai District. Keywords: Agrarian Reform Program, Serdang Bedagai